Descriptive Analysis of the E-Textbook Situation in Quebec - Roy, Normand; Boyer, Priscilla; Lebrun, Monique; Samson, Ghislain (Formation et profession, 2022)
In this study, we will describe and compare the digital components present in Quebec’s e-textbooks for five different subject matters between 2015 and 2018. To do so, we analyzed 133 e-textbooks from secondary 1 to 5 using different observation grids. The added value of technology in e-textbooks was assessed based on three categories: hypertextualization (intertextuality, hypertextuality and hypertext), multimodality (videos, images and animations) and interaction (feedback, activities and simulation). Results showed that half of the e-textbooks are only digitized versions of the paper textbooks. The other half introduce different varieties of multimedia. To conclude, we will propose a reflection on the value of e-textbooks in the high school system.